2009
DOI: 10.1128/aem.02043-08
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Study of Shiga Toxin-Producing Escherichia coli Shedding in Sheep Feces: Persistence of Specific Clones in Sheep Flocks

Abstract: To provide information on the persistence and maintenance of colonization with Shiga toxin-producing Escherichia coli (STEC) in sheep, pulsed-field gel electrophoresis analysis of STEC isolates (n ‫؍‬ 145) belonging to serogroups O5, O91, and O146 from 39 healthy animals was performed in a 12-month longitudinal study carried out with four sheep flocks. At the flock level as well as the individual-animal level, the same clones were obtained on sampling occasions separated by as much as 11 months.Shiga toxin-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
0
8
1
Order By: Relevance
“…The serotypes that have been most frequently reported to have been found in sheep are O5, O91, O117, O128, and O146. Several serotypes found in sheep, such as O5, O26, O91, O128/O128:H2, and O146:H8, have also been isolated from humans in clinical cases (2,3,4,13,29,47,48,50,51). Our findings in sheep also differ from those in previous studies, but the one similarity we detected, represented by O91:H14, is closely related to serotypes that were reported in cases of human disease.…”
Section: Discussioncontrasting
confidence: 57%
“…The serotypes that have been most frequently reported to have been found in sheep are O5, O91, O117, O128, and O146. Several serotypes found in sheep, such as O5, O26, O91, O128/O128:H2, and O146:H8, have also been isolated from humans in clinical cases (2,3,4,13,29,47,48,50,51). Our findings in sheep also differ from those in previous studies, but the one similarity we detected, represented by O91:H14, is closely related to serotypes that were reported in cases of human disease.…”
Section: Discussioncontrasting
confidence: 57%
“…This indicated that farm-raised sika deer has become natural reservoir for pathogenic E. coli O157 in Northeastern China. The dominant serogroups of the E. coli isolates in this study were markedly different from those of diarrheic sheep flocks (O5, O6, O76, O87, O91, O123, O128, O146, O166 and O176) and cattle calves (O56, O78, O8 and O164) [3], [16]. The observed difference in serogroups among farm-raised sika deer, livestock and wild animals might be ascribed to their different feeding managements, habitats and antimicrobials ingests.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, increasing interest has been given to antimicrobial-resistant pathogenic bacteria from various domestic animals and their habitats. Antimicrobial-resistant bacteria have been detected in a variety of domestic animals and the environments that are affected by stockbreeding [2], [3]. E. coli , a type of bacteria common in the intestine of warm-blooded animals, was widely used as an indicator of fecal contamination in drinking water system assessment and food safety evaluation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Little information on the integron content of S. boydii and S. dysenteriae isolates is available, but in our study, harbouring a class 1 integron among either Shigella spp. and is considered a molecular typing tool with high discriminatory power for detection of outbreaks [24,35] and longitudinal observation of bacterial populations [36,37]. Class II integrons (intI2) were detected in only 24 % of S. dysenteriae and 33 % of S. boydii AM-resistant isolates.…”
Section: Discussionmentioning
confidence: 99%